Pemanfaatan Odoo.com sebagai Platform Sistem Informasi Penjualan pada Warung Bakso Mulyo Ditinjau dari Perspektif Sosiologi Teknologi - Melda Agnes Manuhutu; Natasya Virginia Leuwol; Lilian Lilian; Samuel Samuel; Desi Desi; Dewi Dewi; Lulu Jola Uktolseja (Lembaga Pengembangan Kinerja Dosen, 2025)
The rapid development of information technology has had a significant impact on various sectors of life, including micro-enterprises such as meatball stalls. Amidst increasingly fierce competition and the need for operational efficiency, many micro-enterprises are shifting from manual management systems to digital systems. This study aims to explain the background, objectives, and benefits of utilizing information technology in managing meatball stalls, with a focus on the implementation of the Odoo application as a business management solution. Odoo is an open-source Enterprise Resource Planning (ERP) system that offers various functional modules such as Point of Sale (POS), inventory management, accounting, and Customer Relationship Management (CRM). Through the implementation of Odoo, meatball stalls can manage various operational aspects in an integrated manner, from recording sales transactions, managing raw material stock, financial reporting, to customer relations. The results of this technology implementation show significant improvements in data recording accuracy, service speed, and ease of decision-making based on accurate and real-time data. In addition, this technology also provides opportunities for stall owners to develop their businesses more professionally and competitively. Thus, the integration of information technology like Odoo not only improves efficiency and productivity but also contributes to economic growth by strengthening the micro-enterprise sector. This digital transformation is expected to be a strategic step in realizing a modern meatball stall that can compete in the digital era.